TSHoma: A CASE OF MISTAKEN IDENTITY - Albert, Chong Li Ren; Lin, Chan Pei; Sieng, Florence Tan Hui (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND TSH-secreting pituitary tumours are rare causes of hyperthyroidism. Its diagnosis is often delayed due to its uncommon presentation. CASE We report a case of TSHoma in a female initially misdiagnosed as Graves’ disease. A 36-year-old female was diagnosed with Graves’ disease by a general practitioner since 2016 following symptoms of palpitations and weight loss. There was no family history of thyroid disease. She was treated with carbimazole for 6 years before receiving radioactive iodine 15 mCi in May 2022. However, 5 months post RAI, her FT4 remained elevated, ranging from 34.1- 39.1 pmol/L (Normal: 12.3- 20.2 pmol/L) with high TSH of 7.12-10.1 mIU/L (Normal: 0.3-3.94 mIU/L). She was restarted on carbimazole and referred to the endocrine unit. On retrospective review, prior to RAI, she had raised FT4 and TSH levels as well. She also reported intermittent headaches for ten years but no visual disturbances and menstrual irregularities. She was clinically euthyroid. Pulse rate was 70/min and regular without beta blocker. She had a small diffuse goitre but no thyroid eye signs, visual field was normal. Thyroid ultrasound showed diffuse thyroid gland enlargement. Additional testing showed no feature of assay interference. Sex-hormone binding globulin was elevated at 190 nmol/L (Normal: 30-90). Prolactin and cortisol were within normal range. MRI of the brain showed a heterogenous sellarsuprasellar mass measuring 2.0 x 2.5 x 2.4 cm. Six months post RAI she had normal FT4 and FT3 on carbimazole 5 mg daily, but TSH was elevated at 65.2 mIU/L. Carbimazole was discontinued and she was scheduled for transsphenoidal surgery. CONCLUSION In patients with discordant thyroid function results, the possibility of TSHoma should be considered after excluding assay interference and thyroid hormone resistance. Failure to recognize central hyperthyroidism (high FT4 with inappropriately normal or high TSH) can lead to delayed or inappropriate treatment such as RAI ablation with risk of tumour expansion.